Camera lucida : reflections on photography - Barthes, Roland (Hill and Wang, 2010)
Camera Lucida, Roland Barthes's personal, wide-ranging, and contemplative volume--and the last book he published--finds the author applying his influential perceptiveness and associative insight to the subject of photography.